The Recreational Capacity of the Zones of the Ukrainian National Natural Parks - Poletayeva, L. N.; Safranov, T. A. (Man and Environment. Issues of Neoecology, 2021)
Purpose.  To determine the recreational capacity of the territories of several National Natural Parks (NNPs) of Ukraine, as well as the recreational capacity of the tourist trails of these parks.Methods. The methodological basis of the study is based on a critical analysis of the current approaches to the assessment of a recreational facilities of the Ukrainian NNPs. Various published data sources as well as the data, regarding to the recreational renewal capacity of the territories of the NNPs acquired during own research was used.Results. The area of the reserved core that is larger than a one third of the entire area of the park may be seen in only few parks. Most of the NPPs have an insufficient size of the protected areas. This indicate an unstable and severely disturbed ecological conditions, which threatens the conservation of the biological diversity in these parks. That’s why the increase of the protected areas of these NNPs is highly advisable. In addition to all above, the area of the NNP special use zone should be smaller than the area of the regulated recreational area, which plays a certain environmental role; it can be decreased in a favor of the stationary recreational zone if needed. Unfortunately, these conditions are not met for the most of the studied NPPs. That’s why it is advisable to optimize the functional zoning of the NNPs, which will effectively protect the unique natural complexes and will let use them for the recreational purposes. The capacity, the degree of the resistance to the recreational loads, the level of improvement and the capacity of the tourist routes in each of the spoken NNPs were analyzed. The main criteria for choosing the studied NNPs were their representativeness or representation in terms of a variety of the accommodating regions, the availability of the data based on the physical and geographical characteristics, the length of the tourist routes and the statistcs of the visitors per year.  The recreational capacity for the summer season of some NPPs of Ukraine was calculated, while taking into account the standards for each type of the natural complex for the zones of stationary and regulated recreation. Potentially, these zones may be expanded replacing the parts of the reserved special use zone. An assessment of the capacity of some tourist trails of the barely improved NPPs for an unstable and stable category of natural landscape complexes was given. Conclusions. The recreational potential of the researched Ukrainian NPPs is currently underutilized, but with the increase in the flow of the recreants, the recreational areas that are poorly equipped as well as the trails may lead to a deterioration in the state of the natural ecosystems. The functional zones of the stationary and of the regulated parts of the recreational areas of the NNPs may be expanded by migrating some types of the recreational activities to the special use zone of the parks. It is vital to expand the list of the recreational services for recreants, to strive the level of improvement of the tourist trails of the NNPs. If the natural healing resources are present on the territories of the NNPs, it is advisable to organize some centers for the sanatorium treatment, medical and socio-psychological rehabilitation, which will contribute to the creation and an improvement of the medical and the health infrastructure, the activation of recreational activities and the increase in the efficiency of the functioning of the NNP.